2022
DOI: 10.3390/su14031465
|View full text |Cite
|
Sign up to set email alerts
|

Design of Social Responsibility Incentive Contracts for Stakeholders of Megaprojects under Information Asymmetry

Abstract: Social responsibility is essential to the sustainable development of megaprojects. A transparent and symmetrical information-sharing mechanism is an important guarantee for promoting megaproject stakeholders to fulfill their social responsibilities and improve project efficiency. Aiming at the problems of megaproject subcontractors concealing social responsibility information, which leads to unsmooth information channels and low project efficiency, this paper compares and analyzes the single-stage revenue-shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…, 2019), institutional theory (Xie et al. , 2021, 2022) and principal-agent theory (Xue et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2019), institutional theory (Xie et al. , 2021, 2022) and principal-agent theory (Xue et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Three main streams stem from the existing studies. A first literature stream explores the antecedents of MSRB from a range of perspectives, including personal psychological traits of top managers (Lin et al, 2018), external and internal factors (Xie et al, 2019), institutional theory (Xie et al, 2021(Xie et al, , 2022 and principal-agent theory (Xue et al, 2022). The second literature stream predominantly involves the effects of MSRB on interesting objectives, such as project performance (He et al, 2019), industry sustainability (Ma et al, 2019), organisational financial performance and social performance (Ma et al, 2021).…”
Section: Megaproject Social Responsibility Behaviour 4415mentioning
confidence: 99%
“…Examining the Impact of Corporate Governance Mechanisms on the Commitment of Managers, Youngjoo Lee(2022) suggested that managers may use the IPO lockup as a commitment device that complements corporate governance mechanisms in reducing investor concern about the moral hazard problem of managers when small and venture companies go public. Because social responsibility is essential to the sustainable development of megaprojects, Feng Xue et al(2022) argued that incentive contracts with multiple indicators in stages can effectively encourage subcontractors to disclose social responsibility information, and reduce information asymmetry, therefore enhancing social responsibility and improving overall project efficiency. Fuad Basis et al(2022) proposed that policymakers should instruct all hospitals to publish LOS (length of stay) data, regulate referrals to (emergency department ) EDs, and find an optimal LOS that will reduce competition, non-urgent visits, and moral hazard.…”
Section: Moral Hazardmentioning
confidence: 99%
“…Lu et al (2018) pointed out that, although CSR programs are detrimental to the sustainable financial performance of construction companies in the short term, they are beneficial to the improvement of sustainable financial performance in the long term. Transparent and symmetric information-sharing mechanisms are an important guarantee to push stakeholders of megaprojects to fulfill their CSR and improve project efficiency (Xue et al, 2022). PBOs must consider CSR implementation as a long-term strategy that helps companies create value and gain trust and respect of consumers (especially partners), as well as the general public (Nguyen, 2021).…”
Section: Introductionmentioning
confidence: 99%